Adaptation financing as part of a global climate agreement: Is the adaptation levy appropriate? - Klaus Eisenack (University of Oldenburg, Department of Economics, 2011)
The negotiations for a global climate agreement recognize that substantial and additional funds need to be generated for assisting adaptation in developing countries. Currently, the 2% adaptation levy (AL) on the clean development mechanism (CDM) is intended to serve this purpose under the Kyoto Protocol. This paper analyses whether such an arrangement can achieve its objectives, and thereby discusses its future prospects. Can it deliver the funds needed for adaptation, and are they additional? As the AL is facutally a tax on emission trading, does it cause a significant excess burden? How do the transfers from CDM and AL depend on the commitments to reduce greenhous gas emissions, such that the AL may alter the incentives for reaching a global agreement? I address these questions with a partial equilibrium model based on recent marginal abatement cost estimates for 2020. While former studies have focussed on single values for the AL, this paper determines the expected transfers from CDM and AL for a spectrum of emission reduction targets and the full range of AL levels. The paper shows that the revenues from a 2% AL are neglectable compared to the requirements. Even when the AL is increased to maximize transfers in the presence of ambitious emission reduction targets, the revenues are not sufficient (e.g. 15 billion for a 30% reduction target and an 47% AL). These revenues are mostly subtracted from the CDM transfers, such that very little additional funds can be raised (e.g. 2.4 billion under the latter assumptions). There are indeed detrimental effects of the AL for reaching a global agreement, that are nevertheless relatively small. While the excess burden of the AL is small in terms of social cost, it accounts for more than 85% of the additional funds. This supports the overall conclusion that (i) the AL slightly disfavors agreements for climate protection, (ii) is far from sufficient to raise additional funds, and (iii) does this at comparatively high social costs.
Keywords: 330; adaptation to climate change; abatement; CDM; developing countries; transfer payments